Pengaruh Return on Equity (ROE), Current Ratio (CR), Debt to Equity Ratio (DER) dan Total Asset Turnover (TATO), Terhadap Harga Saham Perusahaan Manufaktur di Bursa Efek Indonesia (Study Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia Tahun 2018-2020) - Rif’atul Himmah; Ronny Malavia Mardani; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract Investment in the capital market is a big attraction for investors, because they have the hope of optimal profits. An investor is generally led to always follow market developments or market prices. An investor should not only see the net profit generated by the company but also analyze the financial statements. At the beginning of 2017, the basic and chemical industry sector on the Indonesia Stock Exchange managed to record a fairly high growth. This growth was supported by stocks originating from several sub-sectors including the pulp and paper sub-sector, animal feed sub-sector, and also the chemical sub-sector. Although in 2020, the average performance of issuers decreased due to the COVID-19 pandemic, but in the last month of March 2021, the basic and chemical industry sector rose to 2.39%. this will attract investors' desire to invest in manufacturing companies whose sources of growth are increasing Keywords: Inflation, Exchange Rate, Interest Rate and The Composite Stock Price Index